2014
DOI: 10.1016/j.toxrep.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine induces pancreatic cancer cell death by enhancing reactive oxygen species and DNA damage

Abstract: Pancreatic cancer is one of the most deadly cancers with a nearly 95% mortality rate. The poor response of pancreatic cancer to currently available therapies and the extremely low survival rate of pancreatic cancer patients point to a critical need for alternative therapeutic strategies. The use of reactive oxygen species (ROS)-inducing agents has emerged as an innovative and effective strategy to treat various cancers. In this study, we investigated the potential of a known ROS inducer, piperlongumine (PPLGM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 24 publications
(33 reference statements)
1
48
0
1
Order By: Relevance
“…In this study, our goal was to more fully understand the underlying mechanisms mediating PL-induced pancreatic cancer cell death. While we recently showed that PL inhibits pancreatic cancer progression in a mouse model by elevating ROS and enhancing DNA damage, 7 the specific events leading to DNA damage and cell death have not been previously identified.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In this study, our goal was to more fully understand the underlying mechanisms mediating PL-induced pancreatic cancer cell death. While we recently showed that PL inhibits pancreatic cancer progression in a mouse model by elevating ROS and enhancing DNA damage, 7 the specific events leading to DNA damage and cell death have not been previously identified.…”
Section: Discussionmentioning
confidence: 97%
“…MIA PaCa-2 cells show similar sensitivity toward PL as other commonly studied pancreatic cancer cell lines PANC-1 and BxPC3. 7 The concentration (10 lM) and duration (6 h) of PL treatment that were selected for this study do not cause significant toxicity toward healthy or cancer cells (unpublished observation). However, it is clear from the results presented in this study that significant changes in gene expression are initiated within hours of PL exposure that eventually lead to cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously suggested that electrophilic small molecules such as buthionine sulfoximine (BSO), piperlongumine (PL), and phenethyl isothiocyanate (PEITC) convey at least part of their toxicity via this mechanism (9,16,39,49,51,56), and all of these drugs have been shown to be selectively toxic to certain in vitro and in vivo tumor models (1,5,13,39). Incubation of tumor cells with piperlongumine and PEITC results in depletion of GSH and elevation of fluorescence from dichloro-dihydro-fluorescein diacetate (DCFH-DA), a cell permeable dye that exhibits increasing fluorescence intensity upon oxidation (9,39,49,56). However, recent comprehensive studies involving a broader class of small molecules suggest that the depletion of GSH is often insufficient to induce death of tumor cells.…”
Section: Innovationmentioning
confidence: 99%